Pengaruh Kompetensi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pt. Home Center Indonesia Retail Cabang Ciputat - Afif Trinanda Rahman; Muhammad Gandung (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study is to determine the effect of competence and work environment on employee performance at PT. Home Canter Idonesia Retail Ciputat Branch, both partially and simultaneously. The method used is quantitative. The sampling technique uses saturated sampling and the sample obtained in this study amounted to 63 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determinant coefficient analysis and hypothesis testing. The results of this study are competence obtained regression equation Y = 11.786 + 0.705X1, correlation coefficient 0.713 means that the two variables have a strong level of relationship. The determination value is 0.508 or 50.8%. Hypothesis testing obtained t count> t table or (7.941> 2.000). Thus H0 is rejected and H1 is accepted, meaning there is a significant influence of competence on employee performance. Work environment, obtained regression equation Y = 13.602 + 0.677X2, correlation coefficient 0.743 means that the two variables have a strong level of relationship. The determination value is 0.552 or 55.2%. The hypothesis test obtained t count > t table or (8.665 > 2.000). Thus, H0 is rejected and H2 is accepted, meaning there is a significant influence of the work environment on employee performance. Competence and work environment on employee performance simultaneously have a significant effect with the regression equation Y = 10.404 + 0.307X1 + 0.442X2. The correlation value of 0.763 means that the independent variable with the dependent variable has a strong level of relationship. The determination coefficient value is 58.2%. The hypothesis test obtained F count > F table or (41.723 > 2.758). Thus, H0 is rejected and Hα is accepted. This means that there is a significant influence of competence and work environment simultaneously on employee performance.